Analisis spasial temporal faktor lingkungan fisik dengan kejadian malaria di kabupaten Banjarnegara - Rizki Wahistina; Lutfan Lazuardi; Sitti Rahmah Umniyati (Berita Kedokteran Masyarakat (BKM), 2018)
Spatial-temporal distribution of physical environmental factors of malaria cases in Banjarnegara of Central JavaPurposeThe study aimed to describe physical environmental factors (temperature, humidity, wind velocity and rainfall) statistically, using graphs/time trends and spatial analysis and to analyze its effect on malaria incidence.MethodThis study used the design of ecological studies with spatial-temporal approach. The data were time series data of months of malaria incident and physical environment factors in Banjarnegara period 2011-2015. Poisson and binomial negative regression models were used to analyze the influence of physical environmental factors with the incidence of malaria.ResultsStatistical, graph/time trend, and spatial analysis indicate that there were correlations between temperature, humidity, wind velocity and rainfall with malaria incidence. Negative binomial regression model was the best. It showed that the temperature in the same year (lag 0), the temperature in the previous two months (lag 2 ) and rainfall on the previous month (lag 1) affected the incidence of malaria.ConclusionThe local government of Banjarnegara needs to consider the physical environment factors in implementing the prevention program.